The Impact of COVID-19 Pandemic on Doctors Lives: A Qualitative Study In Cirebon City, Indonesia - Pratiwi, Witri; Rachmawan, Yogi Puji (CV. Publikasi Indonesia, 2025)
Background: The COVID-19 pandemic makes huge changes in human life, including doctors as frontliners in handling the COVID-19 patients. Studies about the impact of the COVID-19 pandemic on doctor lives are still limited. Objective: To understand and explore doctor experiences as the impact of COVID-19 pandemic to their lives. Methods: This study was a Qualitative study with phenomenology approach. It was carried out on doctors who worked in Cirebon City, Indonesia. Data was collected from 9 May 2020 to 25 May 2020 (almost 2 months after the Indonesian government declared COVID-19 as a national disaster). This study used purposive sampling technique and the number of samples was determined by snowball sampling. Data was collected through recorded in-depth interviews with participants agreement. The interview transcripts were analyzed using Colaizzi's method. The data validation was done through researchers' internal discussions and returning descriptions to participants. Results: There were 6 doctors (3 general practitioners, 1 pulmonologist, 1 internist and 1 cardiologist) participated in this study. The participants were 26-36 years old, mostly women (66.67%), married (66.67%) and lived with family members at home. All of participants were moslem. The workplaces of participants varied, including private practice, primary health care, clinic and hospital with 3-12 years of experience. Based on data analysis, there were 6 emergent themes (psychological effects, changes in social interaction, family bonding, finding and sharing information, hopes, and a meaningful Ramadan as a strength to fight). Conclusions: The COVID-19 pandemic affects the doctor lives in several aspects, including psychological, changes in social interaction, family bonding and religious aspects. Pulmonologist experiences a greater impact compared to other doctors. We recommend that doctors are given psychological assistance and support so they can adapt to life changes in this pandemic. Further researchs to explore the impact of the COVID-19 pandemic on elderly doctors are needed.